2018
DOI: 10.1111/nph.15252
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of an aluminum (Al)‐inducible transcription factor, ART2, revealed a different pathway for Al tolerance in rice

Abstract: High aluminum (Al) tolerance in rice (Oryza sativa) is controlled by a Cys2His2-type zinc finger transcription factor ART1 (Al resistance transcription factor 1). There are five close homologs of ART1 in the rice genome, but the role of these homologs is unknown. We functionally characterized one of the ART1 homologs, ART2, in terms of tissue and spatial expression, subcellular localization, transcriptional activation activity, and phenotypic analysis of the knockout lines. ART2 was localized to the nucleus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
30
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(37 citation statements)
references
References 57 publications
0
30
0
Order By: Relevance
“…In previous works by others, the cellular localization of Arabidopsis STOP1 and STOP1 homologs was assessed by transient expression in onion cells, Arabidopsis protoplasts, protoplasts derived from rice callus, tobacco leaves or Nicotiana benthamiana leaves. In all these assays, the STOP1 proteins, fused to the GFP, were localized in the nucleus (Sawaki et al ., , ; Yamaji et al ., ; Fan et al ., ; Wang et al ., ; Che et al ., ; Daspute et al ., ; Huang et al ., ; Wu et al ., ). In these assays, the growth media used were not Pi deficient or particularly enriched in Fe or Al 3+ .…”
Section: Discussionmentioning
confidence: 99%
“…In previous works by others, the cellular localization of Arabidopsis STOP1 and STOP1 homologs was assessed by transient expression in onion cells, Arabidopsis protoplasts, protoplasts derived from rice callus, tobacco leaves or Nicotiana benthamiana leaves. In all these assays, the STOP1 proteins, fused to the GFP, were localized in the nucleus (Sawaki et al ., , ; Yamaji et al ., ; Fan et al ., ; Wang et al ., ; Che et al ., ; Daspute et al ., ; Huang et al ., ; Wu et al ., ). In these assays, the growth media used were not Pi deficient or particularly enriched in Fe or Al 3+ .…”
Section: Discussionmentioning
confidence: 99%
“…In high Al accumulating species like buckwheat, it has been shown that most of the ART1-regulated gene homologs were not differentially regulated in response to high Al levels 42 . ART2, which is a homolog of ART1 has also been reported to regulate Al toxicity tolerance albeit with a different set of genes 43 . These genes were also not differentially regulated in AR genotype.…”
Section: Discussionmentioning
confidence: 99%
“…These included OsSTAR1 , OsSTAR2 , OsNrat1 , OsALS1 , OsMGT1 , OsFRDL4 , and OsFRDL2 , which are discussed above as rice Al tolerance genes [39,40,65,66,67,98]. The other three genes are OsCDT3 , OsEXPA10, and OsART2 [59,62,63]. OsCDT3 is a small cysteine-rich peptide localized on the plasma membrane and may prevent Al entry into root cells through direct Al binding, therefore, contributing to rice Al tolerance [62].…”
Section: Transcriptional Regulation Of Al Tolerance Genesmentioning
confidence: 99%
“…OsART2, a homolog of OsART1, is highly induced by Al. The knockout of OsART2 resulted in increased sensitivity to Al in rice [59]. However, OsART2 contributes more modestly to Al tolerance than OsART1.…”
Section: Transcriptional Regulation Of Al Tolerance Genesmentioning
confidence: 99%